Assignment 9 (MATH 214 B1) 1. Find equations of the tangent plane and the normal line to the given surface at the specified point. √ (a) z = 4 − x2 − 2y 2 , (1, −1, 1). √ Solution. Let f (x, y) = 4 − x2 − 2y 2 . We have fx = ∂f −x =√ ∂x 4 − x2 − 2y 2 and fy = ∂f −2y =√ . ∂y 4 − x2 − 2y 2 It follows that fx (1, −1) = −1 and fy (1, −1) = 2. Hence, the tangent plane to the surface at (1, −1, 1) has an equation z − 1 = −(x − 1) + 2(y + 1) or x − 2y + z − 4 = 0. The normal line to the surface at (1, −1, 1) has symmetric equations x−1 y+1 z−1 = = . 1 −2 1 (b) x2 y 2 + xz − 2y 3 = 10, (2, 1, 4). Solution. Let F (x, y, z) = x2 y 2 + xz − 2y 3 − 10. Then Fx = 2xy 2 + z, Fy = 2x2 y − 6y 2 , Fz = x. It follows that Fx (2, 1, 4) = 8, Fy (2, 1, 4) = 2, Fz (2, 1, 4) = 2. Hence, the tangent plane at (2, 1, 4) has an equation 8(x − 2) + 2(y − 1) + 2(z − 4) = 0 or 4x + y + z − 13 = 0. The normal line to the surface at (2, 1, 4) has symmetric equations y−1 z−4 x−2 = = . 4 1 1 1 2. Let (a, b, c) be a point on the sphere x2 + y 2 + z 2 = 6. (a) Find equations of the normal line of the sphere at the point (a, b, c). Show that the normal line passes through the origin (0, 0, 0). Solution. Let F (x, y, z) = x2 + y 2 + z 2 − 6. Then Fx = 2x, Fy = 2y, Fz = 2z. It follows that Fx (a, b, c) = 2a, Fy (a, b, c) = 2b, and Fz (a, b, c) = 2c. The normal line to the sphere at (a, b, c) has symmetric equations x−a y−b z−c = = . 2a 2b 2c For (x, y, z) = (0, 0, 0) we have 0−a 0−b 0−c 1 = = =− . 2a 2b 2c 2 Hence, the normal line passes through the origin (0, 0, 0). (b) Let C be the curve of intersection of the sphere with the plane z = 2. Find parametric equations of the line tangent to the curve C at the point (1, −1, 2). Solution. The tangent line is orthogonal to both ∇F and k at (1, −1, 2). We have ( ) ∇F |(1,−1,2) = 2x i + 2y j + 2z k |(1,−1,2) = 2 i − 2 j + 4 k. It follows that ∇F × k = −2 i − 2 j. Thus, the tangent line has parametric equations x = 1 − 2t, y = −1 − 2t, z = 2, 2 −∞ < t < ∞. 3. Find all the second-order partial derivatives of the given functions. (a) f (x, y) = ln (x2 + y 2 ) Solution. We have Consequently, ∂f 2x = 2 ∂x x + y2 and ∂f 2x . = 2 ∂y x + y2 ∂2f (x2 + y 2 )2 − 2x(2x) 2y 2 − 2x2 = = , ∂x2 (x2 + y 2 )2 (x2 + y 2 )2 ∂2f ∂2f 2x(−2y) −4xy = = 2 = , ∂x∂y ∂y∂x (x + y 2 )2 (x2 + y 2 )2 (x2 + y 2 )2 − 2y(2y) 2x2 − 2y 2 ∂2f = = . ∂y 2 (x2 + y 2 )2 (x2 + y 2 )2 (b) g(x, y) = sin (xy) cos y Solution. We have gx = y cos(xy) cos y, gy = x cos(xy) cos y − sin(xy) sin y. Hence, we obtain gxx = −y 2 sin(xy) cos y, gxy = gyx = cos(xy) cos y − yx sin(xy) cos y − y cos(xy) sin y, gyy = −x2 sin(xy) cos y − x cos(xy) sin y − x cos(xy) sin y − sin(xy) cos y. 4. Let g(x, y) = xy for 0 < x < ∞ and −∞ < y < ∞. (a) Find all the first-order and second-order partial derivatives of g. Solution. We have gx = yxy−1 and gy = xy ln x. Moreover, gxx = y(y − 1)xy−2 , gxy = xy−1 + yxy−1 ln x, gyy = xy ln2 x. (b) Find the linear approximation to g at the point (1, 4) and the corresponding remainder. Solution. We have g(1, 4) = 1, gx (1, 4) = 4 and gy (1, 4) = 0. Hence, the linear approximation to g at the point (1, 4) is L(x, y) = g(1, 4) + gx (1, 4)(x − 1) + gy (1, 4)(y − 4) = 1 + 4(x − 1). The corresponding remainder E(x, y) is ] 1[ yc (yc −1)xyc c −2 (x−1)2 +2(xyc c −1 +yc xyc c −1 ln xc )(x−1)(y −4)+ xyc c (ln2 xc )(y −4)2 , 2 where xc = 1 + c(x − 1) and yc = 4 + c(y − 4) with 0 < c < 1. 3 5. Find the second Taylor polynomial of the given function at the origin (0, 0). (a) u(x, y) = ex+y cos(x − y). Solution. We have ux = ex+y [cos(x − y) − sin(x − y)] and uy = ex+y [cos(x − y) + sin(x − y)]. Moreover, uxx = ex+y [cos(x − y) − sin(x − y) − sin(x − y) − cos(x − y)] = −2ex+y sin(x − y), uxy = ex+y [cos(x − y) − sin(x − y) + sin(x − y) + cos(x − y)] = 2ex+y cos(x − y), uyy = ex+y [cos(x − y) + sin(x − y) + sin(x − y) − cos(x − y)] = 2ex+y sin(x − y). Consequently, u(0, 0) = 1, ux (0, 0) = 1, uy (0, 0) = 1, uxx (0, 0) = 0, uxy (0, 0) = 2, and uyy (0, 0) = 0. Thus, the second Taylor polynomial of u at (0, 0) is T2 (x, y) = 1 + x + y + 2xy. (b) v(x, y) = ln(e − x + 2y). Solution. We have vx = −1 e − x + 2y and vy = 2 . e − x + 2y Moreover, vxx = −1 , (e − x + 2y)2 vxy = 2 , (e − x + 2y)2 vyy = −4 . (e − x + 2y)2 Consequently, v(0, 0) = ln e = 1, vx (0, 0) = −1/e, vy (0, 0) = 2/e, vxx (0, 0) = −1/e2 , vxy (0, 0) = 2/e2 , and vyy (0, 0) = −4/e2 . Thus, the second Taylor polynomial of v at (0, 0) is x 2y x2 2xy 2y 2 T2 (x, y) = 1 − + − 2+ 2 − 2 . e e 2e e e 4
© Copyright 2025 ExpyDoc